Technology, Adaptation, and Exports : How Some Developing Countries Got It Right. - Chandra, Vandana, 1957- (World Bank e-Library., 2006)
The literature on technological change and growth has mainly used econometric models to establish that factors, such as the degree of openness, skills, research and development expenditures, number of patents etc., are critical determinants of innovation and its effect on growth. However, this approach fails to explain the role of institutions and policies that created the environment for innovation. Using 10 case studies from developing countries, this book examines how governments fostered technological adaptation through public-private partnerships to develop world-class exporters in high-g.